2017
DOI: 10.32677/ijch.2017.v04.i01.017
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of Typhidot-M with Widal and blood culture in diagnosis of enteric fever

Abstract: Objective: To evaluate the diagnostic utility of Typhidot-M and Widal test in the early diagnosis of enteric fever (EF) in terms of sensitivity and specificity. Methods: The study included 270 children in the age group of 1-18 years admitted to the Department of Pediatrics from November 2012 to February 2014, with fever of 5 days or more and with clinical symptoms and signs suggestive of typhoid fever. Detailed history and clinical examination findings were recorded on a standard pro forma. Complete hemogram (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…e majority of the participants were female, accounting for 67.38% (376/558) of the total sample. e majority of participants were in the age range [11][12][13][14][15][16][17][18][19][20] years (219/558, 39.27%) and were students. According to occupation, respondents that were students were more represented (47.67% (n = 266)), followed by participants working in the private sectors (25.80% (n = 144)).…”
Section: Sociodemographic Characteristics Of Respondentsmentioning
confidence: 99%
See 1 more Smart Citation
“…e majority of the participants were female, accounting for 67.38% (376/558) of the total sample. e majority of participants were in the age range [11][12][13][14][15][16][17][18][19][20] years (219/558, 39.27%) and were students. According to occupation, respondents that were students were more represented (47.67% (n = 266)), followed by participants working in the private sectors (25.80% (n = 144)).…”
Section: Sociodemographic Characteristics Of Respondentsmentioning
confidence: 99%
“…The assay gives good results during early infections with a sensitivity of 68–95% and a specificity of 75–95% [ 15 , 16 ]. An increase in the negative predictive value is important in endemic areas [ 17 ]. Recommendations from the World Health Organization for typhoid rapid antibody testing [ 18 ] and some studies that have evaluated the Typhidot ability to detect antibodies have shown variations in sensitivity and specificity [ 15 ] in different settings.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of the participants were female, accounting for 67.38% (376/558). The majority of participants were in the age range [11][12][13][14][15][16][17][18][19][20] years old (219/558, 39.27%), were students. According to occupation, respondent that were student was more represented (n= 266) with 47.67% follow by participants working in the private sectors (144) with 25.80%.…”
Section: Socio-demographic Characteristics Of Respondentsmentioning
confidence: 99%
“…The assay gives good results during early infections with sensitivity of 68-95% and a speci city of 75-95% [15,16]. An increase of negative productive value is important in endemic areas [17]. According to recommendations from World Health Organization for typhoid rapid antibody testing [18] and some studies that have evaluated the typhidot ability to detect antibodies have shown variations in sensitivity and speci city [15] in different settings.…”
mentioning
confidence: 99%
“…The yield of blood culture is 90% in 1 st week, 75% in 2 nd week followed by reduction to 50% by 3 rd week and 25% by 4 th week 10 . Percentage of positive for blood culture is only 30 to 40 because number of patients start antibiotics before taking blood sample for culture 11 .…”
Section: Introductionmentioning
confidence: 99%